Amelioration of Leigh syndrome induced by mouse blastocyst complementation with a mutant human mitochondrial ATP synthase 6. Issue 3 (12th August 2022) - Yuan, Huijun; Webster, Keith A.; Bhatti, Muhammad Tariq; Hauswirth, William W.; Lewin, Alfred S.; Guy, John
Abstract: Background: Mutation of the m. 8993 T > G ATP6 subunit of ATP synthase causes a maternally inherited Leigh Syndrome (LS), a rapidly fatal encephalomyelopathy in childhood called and related Neuropathy, Ataxia and Retinitis Pigmentosa (NARP) in adults. There is no cure, and relevant animal models are few. Here we describe a novel ATP6 mouse model of LS and preclinical efficacy of a gene therapy approach to neutralize the ATP6 mutation by competition with a mitochondrial targeted adeno‐associated virus serotype 9 (AAV9) vector containing wild‐type ATP6 . Methods: LS transgenic mice with an ATP6 mutation were developed by microinjecting AAV2 modified by a COX8 mitochondrial targeting sequence (MTS) into mouse blastocysts to deliver the human ATP6 gene with a T > G mutation at position 8993 of the mitochondrial genome, responsible for clinical LS DNA, protein, and metabolic assays confirmed functional gene delivery and in depth physiological/clinical assessments supported germline transmission of an LS phenotype. Rescue of LS in this model was evaluated after intravenous injection of mito‐targeted AAV9 containing wild‐type ATP6 followed by reevaluation of phenotypes. Results: LS transgenic mice expressed mutant ATP6 protein in multiple relevant tissues including brain, eye, liver. Mutant ATP6 incorporated into Complex V and conferred decreased ATP synthase efficiency. Mice exhibited hallmarks of the human disease with one or multiple systemic symptoms including early death, paralysis, hunching, vision loss and seizures over six generations. Necropsy revealed spongiform encephalopathy, retinal degeneration, and cardiomegaly. Rescue by mitochondrially directed AAV9 containing wild type ATP6 after disease onset conferred prolonged survival and reduced paralysis. When administered prior to disease onset all treated ATP6 mice survived with evidence of globally improved function. Conclusions: The results are consistent with efficient delivery and expression of foreign genes in mitochondria by AAV vectors directed by MTS and support further development of such strategies via intravenous injection of mitochondrial targeted AAV9 to deliver corrective genes. Abstract : Transgenic A6 mice were developed by germline delivery of AAV2 containing mutant human ATP6 targeted to mitochondria by a COX8 (MTS). Transgenic A6 mice and offspring exhibited hallmarks of human Leigh syndrome with multiple systemic symptoms including early death, paralysis, hunching, vision loss, and seizures. Symptoms were ameliorated by intravenous administration of a similarly mitochondrial‐targeted AAV9 containing a wild‐type human ATP6 allele delivered prior to or after disease onset.